Non-invasive diagnosis and assessment of tricuspid regurgitation and stenosis using one and two dimensional echo-pulsed Doppler. - Veyrat, C (1982)
Twenty normal subjects and 82 patients with valvular heart disease, whose lesions were independently assessed either by cardiac catheterisation and/or at operation, were studied using the pulsed Doppler technique combined with either one or two dimensional echocardiography. Of these, 41 patients had tricuspid lesions, including 40 with regurgitation and nine with stenosis. The tricuspid analogue flow velocity trace and the Doppler frequency spectrum (time interval histogram) were recorded. Characteristic differences were found between the records from subjects with and without tricuspid lesions. In subjects with tricuspid regurgitation there was a systolic negative wave on the analogue velocity display and broadening of the time interval histogram. In subjects with tricuspid stenosis there was an abnormal pattern, and significantly increased duration of the diastolic wave on the analogue velocity trace, again with broadening of the time interval histogram. Sensitivity and specificity ranged between 85 and 95%. The calculated ratio between the measured amplitudes of the systolic and diastolic waves correlated well with independently performed grading of the regurgitation on a three point scale in 85% of cases. Grading of the severity of tricuspid stenosis on a three point scale based on studies of the diastolic Doppler velocity anomalies was the same in 85% of cases as the grading based on established invasive techniques. The addition of two dimensional echocardiography to the pulsed Doppler technique increased the sensitivity for mild lesions.